Teachers professional management through teachers working group in Aceh Province - Murniati AR; Nasir Usman; Muhammad Husen; Ulfah Irani (Faculty of Education, Universitas Negeri Yogyakarta, 2019)
This study aims to describe the implementation of teachers management professional development through the Teachers Working Group. This study is a mixed research conducted in ten districts /cities spread in Aceh Province, involving 37 Elementary Schools. The subject in this study include core teacher, teachers, chairman of the KKKS (Principal Working Group), as well as education offices chosen by purposive sampling. Data were collected through interviews, observation and documentation. Qualitative data analysis carried out by the procedure or steps such as data reduction, data display, and verification. The results showed that: (1) Profile of KKG in general consists of the components: (a) the legal basis, the name, position, and the nature of the organization, (b) the vision, mission, and futuristic goals, (c) membership, management and organizational structure, (d) Basic budget, and (e) the facilities and infrastructure for KKG; (2) the implementation of KKG is done through the regular and development activities; (3) The obstacles encountered in the implementation of KKG include: (a) inadequate facilities and infrastructure are inadequate, (b) financing needs to be improved, (c) the motivation of teachers is still low, (d) the principal supports to include teachers in routine activities are lacking due priority school activities, and (e) the support of local government and education authorities on the development of KKG is still lack; while (4) KKG development management evaluation done with the steps: (a) the supervision and monitoring, evaluation, and feedback.